Kinetics of Quality Change and Estimation of Shelf Life of Red Fruit Chicken Baton (Pandanus conoideus L.) Using the Accelerated Shelf Life Testing (Aslt) Method With the Arrhenius Approach - Pratiwi, Indah; tiasni, Sri (Unpad Press, 2025)
Shredded red fruit chicken (Pandanus conoideus) is easily hydrolyzed and affects it’s quality during storage. This study aims to determine te shelf life of shrreded red fruit chicken and get the most influential parameters in determining the shelf life of shrreded red fruit chicken. The shrreded red fruit chicken to be analyzed was packaged in aluminium foil at 20 ̊ C, 30 ̊ C, and 40 ̊ C, then the moisture content, free fatty acid and peroxide number were observed for 18 days. The result showed that the quality of shrreded red fruit chicken decreased with increasing temperature and storage duration. The increase in water content, free fatty acids and peroxide number of shrreded red fruit chicken followed zero order, with Ea values of 10,346.1 cal/mol, 3,564.4 cal/mol and 9,305.9 cal/mol, respectively. Free fatty acids are most sensitive to deterioration during storage as they have the lowest Ea value.Keywords: Red Fruit Chicken Baton, Shelf Life, Arrhenius Approach.